Modern Approach to the Description of Clinical Cases in Evidence-Based Medicine - Kolenko, Ю. Г.; Volovyk, І. А. (Actual Dentistry, 2025)
Relevance. Case reports and publications play an essential role in the development of medical science and education, although their share among all publications is relatively low. Case reports are part of the hierarchy of evidence and should have their place in evidence-based practice. The purpose: to study the analysis of publications of articles about clinical cases; to formulate a strategy for improving their quality and evidence in the modern journalistic world of healthcare journals and the educational process. Materials and methods. The work’s materials are scientific publications of clinical cases in the field of healthcare. The materials used in the study included publications on the analysis of the history of case reports, their content, and evidence for the period 2000–2024. The search was conducted in the PubMed, Scopus, Web of Science, and Google Scholar databases using the terms ‘clinical incident,’ ‘clinical case,’ ‘case report,’ and ‘clinical case report.’ Results of the study. An essential aspect of having peer-reviewed journals that focus on publishing case reports is that it opens up more opportunities for university clinical departments, their students, postgraduates, or young scientists to contribute to medical science. With the growing number of case reports and changes in journal policies regarding the publication of this evidence, the need for standardization is becoming increasingly important. High-quality case reports are more likely to be produced when authors follow reporting guidelines. Journal policies need to become more integrated, and reporting guidelines must align with international standards to improve the quality of publications. Conclusions. Medical journals have established a rather low-quality coverage of articles on clinical cases. It is important to improve the processes of publishing clinical case reports and focus the editorial boards of medical (dental) journals on adopting guidelines for reporting clinical case reports based on the provisions and guidelines of international expert organizations.